Diphtheria re-emerges in the unimmunized. (2021) - Anderson, Paul; Solomon, Matthew; Ramlatchan, Sidhartha; Banerjee, Paul; Ganti, Latha
Abstract: The authors present a case of a 33-year-old African American male with respiratory diphtheria. The patient was initially assumed to have a peritonsillar abscess before various laboratory tests. He complained of dysphagia, throat pain, and shortness of breath. The patient's physical examination, supported by video laryngoscopy imaging and a CT scan, showed swelling of his pharynx. The patient reports that he was recently incarcerated for one year and did not receive immunizations as a child. Following his diagnosis, the patient was treated and subsequently recovered.